Depression care management for adults older than 60 years in primary care clinics in urban China: a cluster-randomised trial. (April 2015) - Chen, Shulin; Conwell, Yeates; He, Jin; Lu, Naiji; Wu, Jiayan
Summary Background China's national health policy classifies depression as a chronic disease that should be managed in primary care settings. In some high-income countries use of chronic disease management principles and primary care-based collaborative-care models have improved outcomes for late-life depression; however, this approach has not yet been tested in China. We aimed to assess whether use of a collaborative-care depression care management (DCM) intervention could improve outcomes for Chinese adults with depression aged 60 years and older. Methods Between Jan 11, 2011, and Nov 30, 2013, we did a cluster-randomised trial in patients from primary care centre clinics in Shangcheng district of Hangzhou city in eastern China. We randomly assigned (1:1) clinics to either DCM (involving training for physicians in use of treatment guidelines, training for primary care nurses to function as care managers, and consultation with psychiatrists as support) or to give enhanced care as usual to all eligible patients aged 60 years and older with major depressive disorder. Clinics were chosen randomly for inclusion from all primary care clinics in the district by computer algorithm and then randomly allocated depression care interventions remotely by computer algorithm. Physicians, study personnel, and patients were not masked to clinic assignment. Our primary outcome was difference in Hamilton Depression Rating Scale (HAMD) score using data for clusters at baseline and 3, 6, and 12 month follow-up in a mixed-effects model of the intention-to-treat population. We originally aimed to analyse outcomes at 24 months, however the difference between groups at 12 months was large and funding was insufficient to continue to 24 months, therefore we decided to end the trial at 12 months. This trial is registered with ClinicalTrials.gov, number NCT01287494. Findings Of 34 primary care clinics in Shangcheng district, 16 were randomly chosen. We randomly assigned eight clinics to the DCM intervention (164 patients enrolled) and eight primary care clinics to enhanced care as usual (162 patients). There were no major differences in baseline demographic and clinical variables between the groups of patients for each intervention. Over the 12 months, patients in clinics assigned to DCM had a significantly greater reduction in HAMD score than did those in practices assigned to enhanced care as usual (estimated between group difference −6·5 [95% CI −7·1 to −5·9]; Cohen's d 0·8 [95% CI 0·8–0·9]; p<0·0001). The intercluster correlation for change in HAMD total score was 0·07 (95% CI 0·06–0·08). There were no study-related adverse events in either group. Interpretation Clinical outcomes of Chinese adults older than 60 years who had major depression were improved when their primary care clinic used DCM. Primary care-based collaborative management of depression is promising to address this pressing public health need in China. Funding National Institutes of Health, Program for New Century Excellent Talents in Universities of China, Ministry of Education, China